2022
DOI: 10.1002/tox.23624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protective effects of quercetin against cypermethrin‐induced lung toxicity in rats via oxidative stress, inflammation, apoptosis, autophagy, and endoplasmic reticulum stress pathway

Abstract: Cypermethrin (CYP), a type II synthetic pyrethroid, is the most widely used insecticide worldwide. Inhalation of it may cause side effects. This study is aimed to examine potential protection of quercetin (QUE) which is a well-known antioxidant in CYPinduced lung toxicity. Accordingly, 35 Spraque Dawley male rats were divided into five equal groups as follows: I-Control group, II-QUE group (50 mg/kg/b.w. QUE), III-CYP group (25 mg/kg/b.w. CYP), IV-CYP + QUE 25 (25 mg/kg/b.w. CYP + 25 mg/ kg/b.w. QUE), V-CYP + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…Cyp metabolites may lead to hepatic cell damage, producing reactive oxygen species (ROS); thus, oxidative stress is caused [ 10 ]. Furthermore, oxidative stress leads to oxidative damage of lipid content, protein oxidation, and DNA damage [ 11 ], which further activate inflammation and apoptosis in the liver [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyp metabolites may lead to hepatic cell damage, producing reactive oxygen species (ROS); thus, oxidative stress is caused [ 10 ]. Furthermore, oxidative stress leads to oxidative damage of lipid content, protein oxidation, and DNA damage [ 11 ], which further activate inflammation and apoptosis in the liver [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ER is Frontiers in Physiology frontiersin.org essential to the process of alveoli production in the following ways: 1) preserving the function of the mitochondria; 2) correction of growth factor and receptor post-translation modifications; 3) reducing oxidative stress production; and 4) control of inflammation (Chan et al, 2016;Biwer and Isakson, 2017;Koksal et al, 2021). It has been observed that HOX and interferon-gamma increase ER stress in the lungs of newborn mice, thus causing lung damage and the arrival of neutrophils (Ileriturk et al, 2022). Non-etheless, further research is necessary to confirm the exact mechanisms underpinning ER stress and its modulatory involvement in different disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress causes NF‐κB activation which leads to increased expression of pro‐inflammatory cytokines, thus triggering the inflammatory process 30,39–41 . The interaction between ER stress and inflammation has been extensively studied in cell types with metabolic or immune functions, and inflammation has been associated with unfolded protein response (UPR) activation to promote disease development 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress causes NF-κB activation which leads to increased expression of pro-inflammatory cytokines, thus triggering the inflammatory process. 30,[39][40][41] The interaction between ER stress and inflammation has been extensively studied in cell types with metabolic or immune functions, and inflammation has been associated with unfolded protein response (UPR) activation to promote disease development. 38 In many previous studies, it has been reported that organophosphate compounds, including MLT, trigger inflammation by increasing the expression of pro-inflammatory cytokines in various tissues.…”
Section: Discussionmentioning
confidence: 99%